(untitled) (Web of Teachers: Inderscience Research, 2025)
Linguistic theories keep pace with the modern world, which is why they now require significant changes in the theory of foreign language teaching, including the methodology of "Russian as a Foreign Language." RFL is currently a relevant course and stands as an independent science. It is aimed at improving the qualifications and training of future teachers and foreign students.